Construction of ZnO@NiO heterostructure photoelectrodes for improved photoelectrochemical performance - Sahoo, Pooja; Sharma, Akash; Padhan, Subash; Thangavel, R. (International journal of hydrogen energy, 2021)
In this report, a p-n junction has been constructed using ZnO/NiO heterostructured photoelectrode by spin coating NiO layers over vertically aligned ZnO nanorod arrays to demonstrate its potential in water splitting applications. Before investigating their PEC performance, we thoroughly studied the introduction of NiO layers on the structure, morphology and light absorption property of ZnO nanorods. 9 layered NiO coated ZnO nanorods exhibited optimum photocurrent density of 0.251 mA/cm2 at 0.8 V vs. Ag/AgCl which is attributed to its high absorbance and better charge transfer as recorded from UV–Vis and EIS data. Furthermore, we also studied the effect of (cation (Mg) and anion (Cl)) doping in PEC performance of ZnO nanorods on this optimized sample. Cl_ZnO/NiO showed high Jph of 1.282 mA/cm2 at 1.2 V vs. Ag/AgCl under visible light illumination. The reason behind better photoresponse is its enhanced absorption and well-defined p-n heterojunction between Cl_ZnO and NiO which favoured the separation and transfer of the photocarriers. The results displayed in this work provides a suitable approach of building p-n junction for high performance PEC water oxidation. [Display omitted] •Influence of NiO layers on surface of undoped and doped ZnO nanorods for PEC performance have been demonstrated.•9 layer NiO coated ZnO and Cl_ZnO/NiO heterostructure showed enhanced PEC activity.•The mechanism of PEC water splitting process in ZnO/NiO p-n heterojunction is proposed.